On the development computer, code for determinig the root of equation for transient flight analysis - Khaire Elarosi, Muwfik Faidi (2013)
This thesis presents the governing equation of flight motions which can be used to describe the flight behavior of any type flying vehicles consist of 12 equations described 12 state – space variables involving the aircraft position and aircraft aptitude with respect to the inertial coordinate system and also with respect to their axis body system had been used. These twelve equations are coupling each to others and in the forms highly non linear equation; the numerical approach is required for solving such system equation. The coefficient of system equation can be said as a result of the combination between aircraft’s mass and inertia, aircraft geometry properties and also their aircraft aerodynamics derivatives. The present work is focused in the development computer code which allows in manner of determining the root of equation of the 12 equations which described the flight behavior for particular airplane. Through determining the root of equation one will able to carry out a non linear transient analysis such as aircraft at landing approaches gust response and pilot initiated maneuvers.